Design, synthesis, and molecular docking studies of N-substituted sulfonamides as potential anticancer therapeutics - Ibrahim T. Babalola, Ph.D; Garba Suleiman, M.Sc. (Journal of Taibah University Medical Sciences, 2024)
الملخص: أهداف البحث: كان الهدف من هذه الدراسة هو تصميم وإتاحة السلفوناميدات المضادة للسرطان عن طريق اقتران الأمينات وكلوريد الدانسيل مع البدائل الإستراتيجية. وباستخدام تقنيات الرنين المغناطيسي النووي ومطياف الكتلة، تم تشخيص الهياكل المركبة. أيضا، تم استخدام تحليل الالتحام الجزيئي لمعرفة مدى ارتباط السلفوناميدات المصنوعة حديثا بـ 5-أسيتاميدو-1،3،4-ثياديازول-2-سلفوناميد، وهو هدف دوائي محتمل. استلزم هذا التقييم مقارنة ارتباطاتها الملزمة بتلك الموجودة في عقار الأسيتازولاميد المعروف. طريقة البحث: تم تصنيع السلفوناميدات عن طريق اقتران الأمينات وكلوريد الدانسيل في ظل ظروف مواتية للغاية. أدرجت السلفوناميدات المصممة بدائل ذات موقع استراتيجي لنقل خصائص بيولوجية متنوعة. تم التحقق من صحة الهياكل المركبة باستخدام الرنين المغناطيسي النووي وأطياف الكتلة. تم إجراء تحليل الالتحام الجزيئي لتقييم الارتباطات الملزمة للسلفوناميدات المركبة مع الهدف الدوائي المحتمل 5-أسيتاميدو-1،3،4-ثياديازول-2-سلفوناميد. النتائج: تم بنجاح تصنيع السلفوناميدات من خلال اقتران الأمينات وكلوريد الدانسيل. أكد التحقق من صحة الهياكل المركبة باستخدام الرنين المغناطيسي النووي وأطياف الكتلة هوياتها الكيميائية. كشف تحليل الالتحام الجزيئي أن السلفوناميدات المُصنّعة أظهرت ارتباطات ربط تتراوح من -6.8 إلى -8.2 كيلو كالوري / مول مع هدف الدواء المحتمل 5-أسيتاميدو-1،3،4-ثياديازول-2-سلفوناميد. الأهم من ذلك، أن جميع المشتقات أظهرت ارتباطات ربط متفوقة مقارنة بالأسيتازولاميد (-5.25 سعرة حرارية/مول). الاستنتاجات: أتاح اقتران الأمينات وكلوريد الدانسيل التوليف الفعال والمباشر للسلفوناميدات. إن التصميم الاستراتيجي للسلفوناميدات مع بدائل محددة سيوفر خصائص بيولوجية متنوعة، بما في ذلك إمكانية النشاط المضاد للسرطان. إن توضيح المركبات المحضرة باستخدام الرنين المغناطيسي النووي وأطياف الكتلة أكد بنيتها. أظهر تحليل الالتحام الجزيئي أن السلفوناميدات المصنعة أظهرت ارتباطات مواتية مع هدف الدواء المحتمل 5-أسيتاميدو-1،3،4-ثياديازول-2-سلفوناميد. والجدير بالذكر أن جميع المشتقات أظهرت ارتباطات ربط أعلى تتراوح من -6.8 إلى -8.2 كيلو كالوري/مول من عقار الأسيتازولاميد الموصى به (-5.25 كيلو كالوري/مول)، مما يشير إلى إمكاناتها كنظائر فعالة للغاية لمزيد من التحقق من الصحة في علاج السرطان. Abstract: Objectives: The goal of this study was to design and enable development of anticancer sulfonamides by coupling amines and dansyl chloride with strategically selected substituents. The synthesized structures were characterized by NMR and mass spectrometry. In addition, molecular docking analysis was used to determine the binding ability of sulfonamides toward 1AZM, a possible drug target, as compared with that of the well-known drug acetazolamide. Methods: Sulfonamides were synthesized by coupling amines and dansyl chloride under highly favorable conditions. The designed sulfonamides incorporated strategically positioned substituents to impart diverse biological properties. The synthesized structures were validated with NMR and mass spectra. Molecular docking analysis was performed to evaluate the binding affinities of the synthesized sulfonamides with the potential drug target 1AZM. Results: The synthesis of sulfonamides through the coupling of amines and dansyl chloride was successfully achieved. The validation of the synthesized structures with NMR and mass spectra confirmed their chemical identities. Molecular docking analysis revealed that the synthesized sulfonamides displayed binding affinities ranging from −6.8 to −8.2 kcal/mol toward the potential drug target 1AZM. Importantly, all derivatives exhibited superior binding affinities to acetazolamide (−5.25 kcal/mol). Conclusions: The coupling of amines and dansyl chloride enabled efficient, straightforward sulfonamide synthesis. The strategic design of sulfonamides with specific substituents endows diverse biological properties, including potential anti-cancer activity. The elucidation of the synthesized compounds with NMR and mass spectra confirmed their structures. Molecular docking analysis demonstrated that the synthesized sulfonamides exhibited favorable binding affinities toward the potential drug target 1AZM. Notably, all derivatives displayed higher binding affinities, ranging from −6.8 to −8.2 kcal/mol, than the recommended drug acetazolamide (−5.25 kcal/mol), thus suggesting their potential as highly effective analogues for further validation in cancer therapy.